2018
DOI: 10.7717/peerj.5419
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of competition and environmental drivers on the growth of the endangered coral Mussismilia braziliensis (Verril, 1867)

Abstract: Most coral reefs have recently experienced acute changes in benthic community structure, generally involving dominance shifts from slow-growing hard corals to fast-growing benthic invertebrates and fleshy photosynthesizers. Besides overfishing, increased nutrification and sedimentation are important drivers of this process, which is well documented at landscape scales in the Caribbean and in the Indo-Pacific. However, small-scale processes that occur at the level of individual organisms remain poorly explored.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“…Our analysis shows that more than half of South Atlantic coral species are tolerant to turbid environments, which is more than twice than the proportion recorded for the Caribbean and more than three times higher than that for the Indo-Pacific (Figure 1). An emblematic example is Mussismilia braziliensis, an endemic species which is one of the main South Atlantic reef-builders, that displays higher growth rate and reproduction effort when found in more turbid conditions (Pires et al, 2011;Ribeiro et al, 2018). In addition, turbid inshore reefs in the South Atlantic often display higher coral cover and abundance than less turbid offshore reefs, particularly Montastraea cavernosa (Francini-Filho et al, 2013;Loiola et al, 2019).…”
Section: Turbidity Tolerancementioning
confidence: 99%
“…Our analysis shows that more than half of South Atlantic coral species are tolerant to turbid environments, which is more than twice than the proportion recorded for the Caribbean and more than three times higher than that for the Indo-Pacific (Figure 1). An emblematic example is Mussismilia braziliensis, an endemic species which is one of the main South Atlantic reef-builders, that displays higher growth rate and reproduction effort when found in more turbid conditions (Pires et al, 2011;Ribeiro et al, 2018). In addition, turbid inshore reefs in the South Atlantic often display higher coral cover and abundance than less turbid offshore reefs, particularly Montastraea cavernosa (Francini-Filho et al, 2013;Loiola et al, 2019).…”
Section: Turbidity Tolerancementioning
confidence: 99%
“…Secondary metabolites produced in response to competitive pressure allow them to survive. Many scientific studies have shown the advantages of possessing these secondary metabolites to survive [12][13][14][15]. Of the more than 33 currently known phyla, 97% are present in and 45% are exclusive to the marine ecosystem [16].…”
Section: Introductionmentioning
confidence: 99%
“…Spatial variation in growth and other demographic patterns among parrotfishes has been associated to sex, fishing effort and resource quality/availability (Gust, Choat & Ackerman, 2002; Taylor & Choat, 2014; Lessa et al, 2016). Across the Abrolhos Bank, there is high cross-shelf variability in environmental conditions and fishing effort (Bruce et al, 2012; Freitas et al, 2011; Freitas et al, 2014; Moura et al, 2011; Moura et al, 2013; Ribeiro et al, 2018), coinciding with the sharp demographic partition between our samples from coastal (slower-growth and ages <9 years) and offshore reefs (faster growth and ages between 3–22 years) (see Fig. 8 and Table 1).…”
Section: Discussionmentioning
confidence: 65%
“…The region encompasses South Atlantic’s largest reefs (20% of the area) and rhodolith beds (∼40%), the two benthic megahabitats where parrotfishes are common. The region is under the synergistic effects of climatic and local anthropogenic stressors (Bruce et al, 2012; Ribeiro et al, 2018). Abrolhos is Brazil’s main reef fisheries ground (Freitas et al, 2014) and bears the country’s first no-take National Marine Park (910 km 2 , declared in 1983) and two community-based Extractive Reserves (ERs), Cassurubá (1,010 km 2 , 2009) and Corumbau (815 km 2 , 2000).…”
Section: Methodsmentioning
confidence: 99%